2012
DOI: 10.1371/journal.pone.0036938
|View full text |Cite
|
Sign up to set email alerts
|

Malabaricone-A Induces A Redox Imbalance That Mediates Apoptosis in U937 Cell Line

Abstract: BackgroundThe ‘two-faced’ character of reactive oxygen species (ROS) plays an important role in cancer biology by acting both as secondary messengers in intracellular signaling cascades and sustaining the oncogenic phenotype of cancer cells, while on the other hand, it triggers an oxidative assault that causes a redox imbalance translating into an apoptotic cell death.Principal FindingsUsing a tetrazolium [{3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl}-2H-tetrazolium] based cell via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 42 publications
1
30
0
Order By: Relevance
“…We have found that treatment of the EAC cells with the compounds increased ROS generation by more than 2fold. Researchers have established that cancer cells have higher basal level of ROS and any agent that increases ROS generation is termed chemotherapeutic agent (Manna et al, 2012) [45]. In the present study we have shown that our compounds increased the level of ROS in EAC cells which ultimately led to EAC cell death (Fig.…”
Section: Biological Activity Of the Complexessupporting
confidence: 53%
“…We have found that treatment of the EAC cells with the compounds increased ROS generation by more than 2fold. Researchers have established that cancer cells have higher basal level of ROS and any agent that increases ROS generation is termed chemotherapeutic agent (Manna et al, 2012) [45]. In the present study we have shown that our compounds increased the level of ROS in EAC cells which ultimately led to EAC cell death (Fig.…”
Section: Biological Activity Of the Complexessupporting
confidence: 53%
“…To examine the effect of F2 fraction on generation of ROS, CM-H 2 DCFDA – lipid soluble, membrane permeable non-fluorescent reduced derivative of 2,7-dichlorofluorescein was used based on the evidence that the acetate groups of CM-H 2 DCFDA are removed by esterase cleavage intracellularly to produce hydrophilic, non-fluorescent dye Dichlorodihydrofluorescein (DCFH 2 ) which is subsequently oxidized by ROS to form a highly fluorescent product Dichlorofluorescein (DCF). Thus, the fluorescence generated is directly proportional to the quantum of ROS generated [20]. The effect of IC 50 concentration of F2 (18.6 µg/ml for U937, 20.9 µg/ml for THP1, 24.6 µg/ml for HL60, 26.1 µg/ml for Raji) on generation of ROS (0–2 h) was measured in cells (2.5×10 5 /ml).…”
Section: Methodsmentioning
confidence: 99%
“…To monitor the levels of reactive oxygen species (ROS) irrespective of their site of generation, PBMCs (5×10 5 ) were stained with CMH 2 DCFDA (5 μM, 30 min, 37°C) and fluorescence of CMDCF acquired on a flow cytometer [10].…”
Section: Measurement Of Cellular Oxidant Statusmentioning
confidence: 99%
“…To measure the levels of non-protein thiols, PBMCs (5× 10 5 ) were initially incubated at 37°C for 30 min in an ATP depletion buffer (21 mM HEPES buffer, 137 mM NaCl, 5 mM KCl, 0.7 mM NaH 2 PO 4 and 20 mM sodium azide, 0.5 ml); cells were then washed with PBS, stained with CMFDA (50 nM, 15 min, 37°C) and fluorescence of CMF was acquired on a flow cytometer [10].…”
Section: Measurement Of Cellular Oxidant Statusmentioning
confidence: 99%